2016
DOI: 10.1007/s12035-016-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical and Pharmacological Characterization of Stem-Like Cells in Human Pituitary Adenomas

Abstract: The presence and functional role of tumor stem cells in benign tumors, and in human pituitary adenomas in particular, is a debated issue that still lacks a definitive formal demonstration. Fifty-six surgical specimens of human pituitary adenomas were processed to establish tumor stem-like cultures by selection and expansion in stem cell-permissive medium or isolating CD133-expressing cells. Phenotypic and functional characterization of these cells was performed (1) ex vivo, by immunohistochemistry analysis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 63 publications
13
68
0
Order By: Relevance
“…showed self-renewal and also limited differentiation capacity in another study (Würth et al 2016). However, these cells were sensitive to the antiproliferative effect of drugs (in this case, dopamine/somatostatin chimeric agonists), which does not fit with the general concept of therapy resistance of TSC.…”
Section: :3mentioning
confidence: 94%
See 1 more Smart Citation
“…showed self-renewal and also limited differentiation capacity in another study (Würth et al 2016). However, these cells were sensitive to the antiproliferative effect of drugs (in this case, dopamine/somatostatin chimeric agonists), which does not fit with the general concept of therapy resistance of TSC.…”
Section: :3mentioning
confidence: 94%
“…Pronounced expression of DLL1, JAG1, HES1, NOTCH1 and NOTCH2 was found in the pituitary tumor SP (Mertens et al 2015) (Table 1) while other candidate TSC populations (i.e. tumorspheres and CD133 + cell populations) showed upregulation of DLL1, JAG2, NOTCH1 and NOTCH4 (Xu et al 2009b, Würth et al 2016, the latter NOTCH receptor subtype in general is more associated with endothelial cells.…”
Section: Dysregulation Of Notch In Pituitary Tumorigenesismentioning
confidence: 99%
“…A hallmark of tumors is the ability to engraft after transplantation into an appropriate recipient animal. While xenografts in mice are still the gold standard, xenografting in zebrafish is increasing in popularity and examples of transplanting human cancer cell lines (Stoletov et al 2007, Lara et al 2011, patient-derived cancer cells (Gaudenzi et al 2016) or tissues (Marques et al 2009) have been reported. Tumor cells can be engrafted in zebrafish embryos, juveniles or adults, and working protocols have been established that outline the advantages and disadvantages of each approach.…”
Section: Patient-derived Xenografts (Pdxs) In Zebrafishmentioning
confidence: 99%
“…Wurth and coworkers transplanted human pituitary adenoma stem cells (hPASCs) in zebrafish and in NOD/SCID mice (Wurth et al 2016). While there was no 24:10 proliferation of hPASCs in murine hosts up to 8 months after injection, these cells readily engrafted into zebrafish embryos.…”
Section: Patient-derived Xenografts (Pdxs) In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation